Copper T (380 A) and risk of uterine perforation in lactating women: rural scenario - Armo, Meena; Minj, Indu Bala; Triki, Anju Rani; Shrivastava, Namita; Mishra, Sonal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Copper T 380 A is commonly used as PPIUCD as well as Interval contraception in rural areas of Chhattisgarh. Studies have reported that interval insertion of intrauterine device in women during their lactation period is associated with high risk of uterine perforation as compared to postpartum insertion similar as our study. Methods: 50 consecutive women were included, who came in family planning OPD of Chhattisgarh Institute of Medical Sciences (CIMS), a Government Medical College, with history of copper T insertion, during their lactation period, within one year of child birth. The copper T insertion was done by health workers at peripheral health centers with complains of pain lower abdomen, menstrual irregularities, missing thread, vaginal discharge, uterine perforation following Copper T 380 A insertion. Apart from patient’s characteristics such as age and parity etc. the method of detection of the perforation and details of management were analyzed. Results: There was one case of partial uterine perforation, one case of copper T lying in peritoneal cavity, two cases of expulsion and three cases had embedded copper T in the myometrium. Conclusions: The risk of perforation due to copper T 380A insertion in lactating women is slightly high, thus timing of insertion, proper counseling and providers training, which are vital factors for intrauterine device use during lactation period, should be considered seriously so as to minimize the complications.